PORTUGUESE LANGUAGE TEACHING AS PART OF THE BELT AND ROAD INITIATIVE - Pestana, Luís Filipe (2019)
The Portuguese language has been expanding in the People’s Republic of China (PRC). The present state of the economic and commercial relations between China and the Portuguese speaking countries has led to a greater demand for Portuguese language courses, as a way of accessing the job market more easily. President Xi Jinping (Zhang 2017) presented the Belt and Road Initiative signalling that the inclusion of the Portuguese language in this grand strategy will lead to a rising interest in hiring individuals that know it. To understand what is the Belt and Road Initiative and how it may influence Portuguese language teaching in the PRC is a starting point to propose actions that may contribute to the strengthening of the Portuguese language’s role in the AsiaPacific region and adapt to the Chinese job market.